2014
DOI: 10.1016/j.expneurol.2014.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Low brain iron effects and reversibility on striatal dopamine dynamics

Abstract: Iron deficiency (ID) in rodents leads to decreased ventral midbrain (VMB) iron concentrations and to changes in the dopamine (DA) system that mimic many of the dopaminergic changes seen in RLS patient where low substantia nigra iron is a known pathology of the disease. The ID-rodent model, therefore, has been used to explore the effects that low VMB iron can have on striatal DA dynamics with the hopes of better understanding the nature of iron-dopamine interaction in Restless Legs Syndrome (RLS). Using a post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 44 publications
3
42
0
Order By: Relevance
“…Those include an increase in striatal extracellular concentrations of dopamine, a reduction in the density of striatal D2R and an increased tyrosine hydroxylase activity in the ventral midbrain. 12,37 …”
Section: Discussionmentioning
confidence: 99%
“…Those include an increase in striatal extracellular concentrations of dopamine, a reduction in the density of striatal D2R and an increased tyrosine hydroxylase activity in the ventral midbrain. 12,37 …”
Section: Discussionmentioning
confidence: 99%
“…PLMS is very responsive to dopamine treatment suggesting a major dopamine pathophysiology driving the PLMS [4648]. Animal studies have demonstrated that low iron in the SN occurs with the increased striatal dopamine activation [49] as seen in RLS [50] presumably leading to over-activation of compensatory mechanisms producing PLMS. Thus the iron status of the SN is expected to associate with the PLMS motor sign of RLS, as it does in this study.…”
Section: Discussionmentioning
confidence: 99%
“…That may not, however, be true. The iron-deficiency (ID) rodent model, which has demonstrated biological changes that closely mimic the changes seen in RLS [21], does implicate changes in dynamic relation between pre and synaptic function that are more complex than simple attribution of increased TH or decreased D2/3R as the primary insult [23]. Despite the uncertainty of what factors contribute to the dynamic change in the dopaminergic function in RLS, this is also an issue of systems dynamics: brain region, oscillatory state, feedback dynamics and other systems are likely to play primary roles in how dopaminergic system “functions” in RLS.…”
Section: The State Of the Daergic System In Rlsmentioning
confidence: 99%